Applying Ultrasound‐Guided Core Needle Biopsy for Diagnosis of Thyroid Masses: Preliminary Results From a Single Institution. (31st August 2015) - Kim, Yong Hee; Kwon, Hyeong Ju; Kim, Eun-Kyung; Kwak, Jin Young; Moon, Hee Jung; Yoon, Jung Hyun
Abstract : Objectives: The purpose of this study was to investigate the level of conclusive results obtained with ultrasound (US)‐guided core needle biopsy (CNB) and how this method should be applied for diagnosis of thyroid nodules. Methods: From January 2013 to November 2014, US‐guided CNB was performed in 84 thyroid lesions of 83 patients. Based on CNB pathologic reports, thyroid nodules were divided into 2 categories: conclusive (nodules reaching a definite pathologic diagnosis suggesting benignity or malignancy) and inconclusive (nodules that were not able to reach a definite diagnosis because of ambiguous results). Medical records and US examinations were reviewed and compared. Results: The mean age of the 83 patients ± SD was 49.7 ± 14.1 years. Of the 84 thyroid nodules, 73 (86.9%) were diagnosed as benign or malignant and 11 (13.1%) as inconclusive by CNB pathologic analysis. Among the 11 nodules with inconclusive results, the possibility of a follicular neoplasm was suggested in 8 nodules (72.7%). No significant difference was seen in tumor size and US features when comparing the nodules with conclusive and inconclusive results (all P >.05). Conclusions: Ultrasound‐guided CNB may have supplemental roles in addition to US‐guided fine‐needle aspiration for diagnosis of selected cases. A considerable proportion of inconclusive results are seen on US‐guided CNB, especially for diagnosis of follicular lesions, which must be considered when using this method for diagnosis of thyroid nodules.